Symbolic Behavior in Regular Classrooms: A Specification of Symbolic and Non-Symbolic Behavior - Billinger, Stefan (Frontiers in Psychology, 2011)
Students’ capabilities to use symbolic information in classroom setting could be expected to influence their possibilities to be active and participating. The development of strategies for teachers to compensate for reduced capability need specific operational definition of symbolic behavior. Fifty-three students, aged 11 to 13 years old, 29 boys and 24 girls, from three classes in the same Swedish compulsory regular school participated in the current study. After a short training sequence 25 students (47%) were defined as showing symbolic behavior (symbolic), and 28 students (53%) were not (non-symbolic), based on their follow-up test performances. Symbolic and non-symbolic differed significantly on post test performances (p. < .05). Surprisingly, non-symbolic behavior deteriorated their performance, while symbolic enhanced their performance (p. < .05). The results indicate that the operational definition used in the present study may be useful in further studies relating the capability to show symbolic behavior and students’ activity and participation in classroom settings.